Image-based analysis and quantification of ulna morphology for improved implants design. - Ong, Yi Bin. (2012)
Till date, there are inherent difficulties in estimating the size and fit of elbow prosthesis based solely on plain radiographs of patients. As such, a better understanding of the morphology of the proximal ulna will have implications for future prosthetic design, preoperative planning, and cement removal during revision surgery, all of which benefit the patients eventually. Thus, the objective of the project is to define intra-medullary dimensions and morphological relations in cored cadaveric ulnas with a CT-based image analysis program. CT scans of 17 pre-cored and post-cored cadaveric proximal ulnas were analyzed to determine the intra-medullary dimensions using reconstructed 3D models. A local coordinate system was established for the individual ulna. The posterior offset, lateral offset, minimum diameter and maximum diameter of the intra-medullary canal were calculated with respect to the local origin. Generally, the intra-medullary canal in the supine position offsets linearly, 5 mm posteriorly and 19 mm laterally from 0R to 6R, where R represents the radius of the circle fitted to the trochlear ridge. The minimum and maximum diameters of the canal increase from the origin and peak at 2.3R with diameter values of 7.08 ± 1.74 mm and 10.65 ± 2.16 mm respectively. Thereafter, they decrease in a linear fashion till 6R. Our findings support the current tapered component of the proximal ulna stemmed implants and suggest the use of 3D CT scans of the elbow for pre-operative planning and sizing of implants.